Reducing challenging behaviour of adults with intellectual disabilities in supported accommodation: A cluster randomized controlled trial of setting-wide positive behaviour support. (October 2018) - McGill, Peter; Vanono, Leah; Clover, Will; Smyth, Emmett; Cooper, Vivien; Hopkins, Lisa; Barratt, Nick; Joyce, Christopher; Henderson, Kate; Sekasi, Sheila; Davis, Susy; Deveau, Roy
Highlights: An experimental intervention improved the quality of social care in residential settings. Quality of social care improved significantly more than in control settings. Quality of life improved more in experimental settings but not significantly. Challenging behaviour reduced by more than 2/3rds in the experimental group. The intervention was greeted very positively by staff and others. Abstract: Background: Improving the quality of social care through the implementation of setting-wide positive behaviour support (SWPBS) may reduce and prevent challenging behaviour. Method: Twenty-four supported accommodation settings were randomized to experimental or control conditions. Settings in both groups had access to individualized PBS either via the organisation's Behaviour Support Team or from external professionals. Additionally, within the experimental group, social care practice was reviewed and improvement programmes set going. Progress was supported through coaching managers and staff to enhance their performance and draw more effectively on existing resources, and through monthly monitoring over 8–11 months. Quality of support, quality of life and challenging behaviour were measured at baseline and after intervention with challenging behaviour being additionally measured at long-term follow-up 12–18 months later. Results: Following intervention there were significant changes to social care practice and quality of support in the experimental group. Ratings of challenging behaviour declined significantly more in the experimental group and the difference between groups was maintained at follow-up. There was no significant difference between the groups in measurement of quality of life. Staff, family members and professionals evaluated the intervention and its outcomes positively. Conclusions: Some challenging behaviour in social care settings may be prevented by SWPBS that improves the quality of support provided to individuals.